Understanding consumption patterns in the civitas Tungrorum through the identification of the ‘NOOR1’ Ware - Van Kerckhove, Julie; Lepot, Annick; Borgers, Barbara; Willems, Sonja (Rei Cretariae Romanae Fautorum Acta, 2015)
In this article a regionally produced coarse ware, the ‘NOOR1’ Ware, will be used as a case study in an attempt to contribute to the understanding of consumption patterns in the civitas Tungrorum, a frontier zone of the Roman Empire. S. Willems associated the term ‘NOOR1’ with this ware as a Dutch abbreviation of ‘Northern’ 1, because of the northern location of its distribution. We used a specific methodology in order to make this coarse ware recognizable for others and to make it suitable to use in the consumption debate. The concept of consumption and its potential for the interpretation of Roman material culture will be explained briefly. The focus of this paper, however, will be on the used methodology. In an attempt to turn a large amount of sherds into a well-processed dataset suitable to be used as a tool for answering more complex social questions, such as consumer practices, we needed a well thought out methodology. All sherds are studied in hand specimen, using the binocular microscope and in thin section petrography, using the polarising microscope. Based on these findings, the fabric is described in detail and furthermore a new typology is created. By comparing the characteristics and the distribution of this coarse ware to the pottery spectrum and traditions from the civitates Tungrorum and Ubiorum, we are able to make the concept of consumption more tangible.